2019
DOI: 10.14453/aabfj.v13i4.8
|View full text |Cite
|
Sign up to set email alerts
|

Management Accounting and Service Companies' Performance: Research in Emerging Economies

Abstract: Organizations use management accounting information in a variety of ways, and specifically management accounting information that plays a significant role in the effective management process. In addition, management accounting information contributes to the organization's performance by giving feedback on carrying out the strategic plans and completing the work, and consequently enhancing the economy of the country. However, new management accounting systems, due to its externally and futureoriented strategic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…Audit committee characterized among other control mechanisms is considered as an essential role in monitoring and overseeing the management and advising with regards to the usage of internal control systems and preparation of financial statement, as such importance for such control mechanisms and others are mentioned by several studies that done in the literature review (e.g. Hamdan, 2020;Ammar & Ahmad Zuluki, 2017;Alabdullah, 2019;Alabdullah, 2018;Alabdullah, 2017;Alabdullah, 2016;Alabdullah, 2016a;Alabdullah, 2016b;Alabdullah, Nor, & Ries, 2018). A study done by Ahmed et al (2020) investigates the control mechanisms and firm profitability in Oman and found that a positive relationship between all the CG mechanisms is found: gender, ownership, audit committee and board size and firm profitability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Audit committee characterized among other control mechanisms is considered as an essential role in monitoring and overseeing the management and advising with regards to the usage of internal control systems and preparation of financial statement, as such importance for such control mechanisms and others are mentioned by several studies that done in the literature review (e.g. Hamdan, 2020;Ammar & Ahmad Zuluki, 2017;Alabdullah, 2019;Alabdullah, 2018;Alabdullah, 2017;Alabdullah, 2016;Alabdullah, 2016a;Alabdullah, 2016b;Alabdullah, Nor, & Ries, 2018). A study done by Ahmed et al (2020) investigates the control mechanisms and firm profitability in Oman and found that a positive relationship between all the CG mechanisms is found: gender, ownership, audit committee and board size and firm profitability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, using managerial cost accounting to estimate better individual costs of products and services of a company allowing company managers to assess the performance of individuals concerning these costs (Mohr, 2017). Alabdullah (2019) implied the accounting performance measurement is an approach that keeps a company on target to hit its goals. Additionally, it is a system used by both the managers and shareholders of an organization because performance measurements must sync with the organization's strategy to be sufficient.…”
Section: Accounting Based Solutionsmentioning
confidence: 99%
“…Additionally, it is a system used by both the managers and shareholders of an organization because performance measurements must sync with the organization's strategy to be sufficient. Accounting Performance measurements identify the strategies that offer the highest potential for obtaining the corporation's objectives (Alabdullah, 2019).…”
Section: Accounting Based Solutionsmentioning
confidence: 99%
“…It is known through researches done in the whole world that corporate governance (CG) is known as a great instrument in assessing the firms' ability of being functional and strong ( (Alabdullah, Yahya & Ramayah, 2014;Alfadhl et al, 2013;Alfadhl and Alabdullah, 2016;Crifo, Escrig-Olmedo, & Mottis, 2019). CG, together with its mechanisms and structures is very useful to monitor profitability of the firm (Alabdullah, 2019). The best CG reflects better information to make the firm reach its targets and goals; that's to reach the effective level of firm profitability .…”
Section: Introductionmentioning
confidence: 99%
“…This made CG strongly appear in the last few decades in several developed and developing countries. This system appeared before a hundred years but in another form as controlling role that has standards, principles and mechanisms that help different parties (e.g., Alabdullah, 2019;Alabdullah, 2016aAlabdullah, , 2016bAlabdullah, , 2016cAlabdullah, , 2016dAlabdullah, , 2017Alabdullah , Laadjal, Ries, & Al-Asadi, 2018). Its mechanisms are board size, board independency, duality, gender , and ownership structure plus other internal mechanisms .…”
Section: Introductionmentioning
confidence: 99%